Experimental investigation of shear behavior in rectangular concrete-filled steel tubes - Abdullah Alghossoon; Suhaib Almarashdeh; Ahmad Tarawneh; Ra’ed Al-Mazaidh; Eman Saleh; Ghassan Almasabha (Results in Engineering)
Rectangular concrete-filled steel tubes (RCFTs) are gaining traction in high-shear-demand systems, such as coupling beams, panel zones, and shear links. However, current design equations lack precision due to limited research in this area. This study presents an experimental assessment of shear performance in RCFT through a series of full-scale three-point loading tests, considering the effects of shear span-to-depth ratio, width-to-thickness ratio, depth-to-width ratio, and concrete compressive strength. The results demonstrate that the concrete core in rectangular concrete-filled tubes (RCFTs) enhances load distribution on steel tubes, thereby enhancing its ultimate and residual strength as well as its overall ductility. The Failure mechanism is influenced by the shear span-to-depth ratio (a/d), with shear failure occurring at a/d < 0.5, flexural failure at a/d > 2.0, and a combined shear-flexure failure at 0.5 < a/d < 2. The strain distribution observed through Digital Image Correlation (DIC) and the test observations eliminate concerns about slippage, even at short-span ratios indicating efficient utilization of composite action in shear resistance and supporting the applicability of the truss analogy for predicting the load-carrying capacity of RCFTs in shear-critical applications.